2021
DOI: 10.5964/ps.6043
|View full text |Cite
|
Sign up to set email alerts
|

The judgment of personality: An overview of current empirical research findings

Abstract: This article presents an overview of the current state of knowledge in personality judgment research. We discuss accuracy and bias in personality judgments, including types of inter-rater agreement and elements of criteria used to determine levels of agreement and accuracy. We then address 1) the words and phrases that people use to describe one another and themselves, 2) research investigating judgments of targets by perceivers per trait, and 3) research investigating judgments of targets by perceivers on pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
(100 reference statements)
1
5
0
Order By: Relevance
“…Overall, the state of the evidence on the accuracy of personality impressions from faces is mixed with many inconsistent findings. The majority of published studies found above-chance accuracy for extraversion impressions (Naumann et al, 2009;Penton-Voak et al, 2006), which is in line with previous work on personality judgments in more information-rich environments, such as brief face-to-face interactions (Kenny & West, 2008;Letzring et al, 2021). However, some studies did not find evidence for accuracy in spite of similar methods and sample sizes (Ames et al, 2010;Shevlin et al, 2003).…”
Section: Accuracy Of Personality Impressions From Faces: Empirical Ev...supporting
confidence: 81%
See 2 more Smart Citations
“…Overall, the state of the evidence on the accuracy of personality impressions from faces is mixed with many inconsistent findings. The majority of published studies found above-chance accuracy for extraversion impressions (Naumann et al, 2009;Penton-Voak et al, 2006), which is in line with previous work on personality judgments in more information-rich environments, such as brief face-to-face interactions (Kenny & West, 2008;Letzring et al, 2021). However, some studies did not find evidence for accuracy in spite of similar methods and sample sizes (Ames et al, 2010;Shevlin et al, 2003).…”
Section: Accuracy Of Personality Impressions From Faces: Empirical Ev...supporting
confidence: 81%
“…In some studies, perceivers evaluated targets with the same personality questionnaire that was also used by targets (Naumann et al, 2009;Nestler et al, 2012). In others, perceivers' judgments were assessed with simpler rating scales, such as a single 2 Research on the accuracy of personality judgments sometimes distinguishes between different types of accuracy (Back & Nestler, 2016;Biesanz, 2010;Hall et al, 2018;Letzring, 2008;Letzring et al, 2021). Accuracy can be examined at the inter-target or intra-target level.…”
Section: Accuracy Of Personality Impressions From Faces: Empirical Ev...mentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, listing the individual propositions constituting the consensus point by point in a very fine-grained manner (and even numbering them) is highly recommendable (e.g., Letzring et al, 2021), because it makes it easier to call out the particular elements of a consensus that one deems questionable. Sixth, any consensus should always be regarded as preliminary and versioning should probably be the norm.…”
Section: How Shall We Build Consensus?mentioning
confidence: 99%
“…One of us (IT) has repeatedly argued that a six-factor structure is more valid (e.g., Thielmann et al, 2021). One of us (DL) is not even convinced that the source of item-covariation in the relevant studies lies in the targets (Letzring et al, 2021; see also Borkenau, 1990). So, our call for greater openness to explicit consensus-formation clearly is not a covert appeal to finally give in and accept the Big Five as law of the land.…”
Section: Consensusmentioning
confidence: 99%